Isolated changes in femoral version do not alter intra-articular contact mechanics in cadaveric hips. (26th August 2020) - Meyer, Alex M.; Thomas-Aitken, Holly D.; Brouillette, Marc J.; Westermann, Robert W.; Goetz, Jessica E.
Abstract: Abnormal femoral version is a deformity in the angle between the femoral neck and the transcondylar axis of the knee. Both femoral anteversion and retroversion alter passive and active rotation of the hip and are associated with intra-articular or extra-articular impingement. However, little is known about the effect of abnormal femoral version on intra-articular hip contact stresses. To quantify the effect of femoral version on hip contact stress, five cadaveric pelvis specimens were mechanically tested with a hip-specific Tekscan sensor inserted in the joint space. Specimens were oriented in a heel-strike position and loaded with 1000 N of compressive force. Pressure measurements were recorded by the Tekscan sensor with the femur oriented in 0°, 15°, and 30° of version. At the completion of testing, specimens were locked into place at 0° and post-test CT scans were obtained to register the pressure sensor measurements to the joint anatomy. There were minor changes in contact area (<7%) and translation of the peak contact stress location (8.8 ± 7.6 mm). There was no significant change in peak contact stress (p = 0.901) in either the retroverted (0°) or anteverted (30°) conditions relative to normal version (15°) under identical gait-related loading conditions. While abnormalities in patient gait and resultant joint loading caused by femoral version abnormalities may contribute to hip pain, the present findings would suggest that future joint degeneration in hips with version abnormalities are not simply the result of abnormal contact stress induced by joint incongruity due to femoral version abnormalities.